Study Of Poisoning, The Most Prevailing Cause Of Unnatural Death In North Bengal (Journal of Shaheed Suhrawardy Medical College, 2012)
The main aim of this study was to find out the relationship between the postmortem eases of poisoning to other eases. This was a retrospective study carried out in the department of Forensic Medicine, Dinajpur Medical College during the period from July 05 to May 06. The total number of autopsv performed in this period was 360. The result concluded that poisoning is the most predominant cause of all unnatural death in North Bengal. Journal of Shaheed Suhrawardy Medical College Vol 2No.1 June 2010 page 4-5 DOI: http://dx.doi.org/10.3329/jssmc.v2i1.12342